Jay Garrick, the Flash - Adams, Jeremy (Screenwriter) (DC Comics, 2024)
"Jay Garrick, the first speedster to wear the mantle of The Flash, is reunited with his long-lost daughter, Judy. After being pulled from the timeline, Judy returns to a world where she and her dad aren't the only ones that ride the lightning, but is there enough space for her in Jay and Joan's life? And can they keep up with their teenage daughter and make up for lost time? They'll need to figure it out fast as enemies from Jay Garrick's past are targeting his daughter across the decades, in a sinister plot 80 years in the making!--